A highly reactive precursor in the iron sulfide system - Adriana Matamoros-Veloza (Nature Portfolio, 2018)
Mackinawite is commonly assumed to be the first solid phase in the iron sulfide system. Here, the authors report the existence of a highly reactive nanocrystalline solid phase that is a necessary precursor to the formation of mackinawite.